Seminars as a Way of Organizing Teaching - Carmen Niurka Piña Loyola; Aimeé Seife Echevarría; Carmen Margarita Rodríguez Borrell (Medisur)
A literature review was conducted in order to addresses seminars as a way of organizing education. Aspects related to the origin of this type of lesson, its concepts, functions, structure, methodology, types, advantages and some general intellectual and professional skills that can be developed with their use are reflected. We conducted this research in order to provide enough information as to understand the importance of this organizational form of the teaching-learning process and also to endow seminars with a true developing, participatory and educational character.